Tirzepatide versus semaglutide for weight loss in patients with type 2 diabetes mellitus: A value for money analysis. Issue 4 (27th December 2022) - Azuri, Joseph; Hammerman, Ariel; Aboalhasan, Enis; Sluckis, Ben; Arbel, Ronen
Abstract: Aims: Higher doses of the glucagon‐like peptide‐1 agonist semaglutide and, more recently, tirzepatide, a dual glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1 agonist showed a significant reduction in body weight in patients with type 2 diabetes mellitus. However, their comparative value for money for this indication is unclear. Therefore, we aimed to establish which provides better value for money. Materials and Methods: We calculated the cost needed to treat to achieve a 1% reduction in body weight using high‐dose tirzepatide (15 mg) versus semaglutide (2.4 mg). The body weight reductions were extracted from published results of SURMOUNT‐1 and STEP 1 trials, respectively. In addition, we performed a scenario analysis to mitigate the primary differences between the two study populations. Drug costs were based on US GoodRx prices as of October 2022. Results: Using tirzepatide resulted in a weight loss of 17.8% (95% CI: 16.3%‐19.3%) compared with 12.4% (95% CI: 11.5%‐13.4%) for semaglutide. The total cost of 72 weeks of tirzepatide was estimated at $17 527 compared with $22 878 for 68 weeks of semaglutide. Accordingly, the cost needed to treat per 1% of body weight reduction with tirzepatide is estimated at $985 (95% CI: $908‐$1075) compared with $1845 (95% CI: $1707‐$1989) with semaglutide. Scenario analysis confirmed these findings. Conclusions: Tirzepatide provides better value for money than semaglutide for weight reduction.